Strategic framework for corporate social responsibility practices: a study of North-West region of India - Sharma, Anupam (My University, 2013)
In context to India the term CSR might be new but the concept is as old as Indian culture. Previously Hindu’s call it ‘dharmmada’, Muslims call it ‘zakatah’, and Sikhs call it ‘dashaant’. As individuals joined hands to form organizations, the same concept became embedded in the organizations. As India entered the phase of liberalization, increasing number of agencies and firms including the multinational firms have started investment in social sector development. Our economy is exposed to changing market structures and competitive environment. And this practice of donation of money for the social cause or social upliftment of the society has changed with economic reforms. Today the Corporate social responsibility (CSR) goes far beyond the old philanthropy of the past – donating money for a good cause at the end of the financial year– and is instead an all year round responsibility that companies accept for sustainable environment around them, for the best working practices and for the engagement of local communities. Now we need to move towards a challenging measure of corporate social responsibility i.e., how organizations can generalize the concept of CSR to help the society. The present research studies the CSR practices followed by large scale organizations in the North-West region of India in special context to IT, Auto and Fast moving consumer goods Fast moving consumer goods (FMCG) firms in three the areas of health, education and environment. This research also analyses the prospective drivers and barriers in CSR implementation initiatives. Focusing on all these important aspects, CSR will enable the firms to plan their CSR initiatives in a co-ordinated way so that the common benefits can be achieved. This has been done with the help of well-structured questionnaire designed and used as a prime survey instrument for data collection and case studies of 12 major companies have been used. The learning from case study analysis helped to identify the strategic factors in three key areas, viz. health, education and environment. The results inherently reflect that Auto and IT sectors are leading in CSR initiatives and FMCG sector is lagging behind. Auto and IT sector are predominant in all key areas, viz. health, education and environment, while FMCG is more into health initiatives. The results are also indicative of the fact that all three sectors are pursuing environmental CSR activities although the intensity of initiatives is more by auto sector. IT sector is leading in Education initiatives. Inputs from the survey and case studies have helped in designing a strategic framework. The strategic framework focuses on CSR: health, education and environmental CSR initiatives. Finally the strategic CSR framework will help in addressing various societal issues to some extent. Corporate social responsibility links up the role of business in tackling the critical issues like societal development, human development, educational development and environment stability in developing countries like India. The strategic parameters derived on the basis of Carroll’s four responsibility pyramid highlight the weak links in CSR initiatives. The results of strategic parameters suggest that the Indian firms are pursuing CSR initiatives for economic perspectives. Legal, ethical, and philanthropic responsibilities are still far from being fully achieved. Community investment cost saving and improving business performances were the major economic factors. In legal responsibility, regulatory obligations had paramount importance over other legal factors. In ethical responsibility CSR reporting had an edge over other ethical responsibilities. In philanthropic responsibility preserving natural environment and social concerns relating to product/service received higher ratings. Thus, Indian firms need to focus more on ethical and legal responsibilities to rise to the concept of holistic CSR.
PhD
Keywords: Corporate social responsibility; globalization; philanthropy; multinational